Analysis of The Psychological Adaptation of Payangan Coastal Communities Through The Roy Adaptation Model - Nugrahani, Ely Rahmatika (The Indonesian Journal of Health Science, 2023)
Extreme and erratic climate change causes coastal communities to concerns experience, especially for families with livelihood as fishermen. Psychological adaptation was needed to cope with life changes. The purpose of this study was to analyze the adaptability of Payangan Coastal Communities used Roy adaptation Model approach.  this study used descriptive analysis design with cross sectional approach. The sample used in this study were 102 respondents who live on the coast of Payangan Beach using a consecutive sampling technique. This study used logistic regression test. The results obtained psychological adaptation in Payangan Coastal Communities influenced by several factors, namely gender, education, and income. Gender has a positive effect on psychological adaptation because of the character that does not settle in the individual, caused emotional stability and the ability to seek rational problem solving was low. Education has a positive effect on psychological adaptation due to the inability of brain activity in thinking that affects the willingness to learn and the ability to compare problems were low. Income also has a positive effect on psychological adaptation due to public concerns of erratic weather, low income, and uncertain natural conditions.  the psychological adaptation of the Payangan Coastal Communities was low, so special attention is needed to increase their adaptability.